Foreign body ingestion during the COVID-19 pandemic: a retrospective single centre review. Issue 1 (26th July 2021) - Festa, Naomi Tyne; Thakkar, Hemanshoo; Hewitt, Richard; Dhaiban, Manal; Muthialu, Nagarajan; Cross, Kate; De Coppi, Paolo
Abstract : Introduction: During the COVID-19 pandemic in 2020, there were many changes in the provision of healthcare as well as home and educational environments for children. We noted an apparent increase in the number of children presenting with ingested foreign bodies and due to the potential impact of injury from this, further investigated this phenomenon. Method: Using a prospective electronic record, data were retrospectively collected for patients referred to our institution with foreign body ingestion from March 2020 to September 2020 and compared with the same period the year prior as a control. Results: During the 6-month pandemic period of review, it was observed that 2.5 times more children were referred with foreign body ingestion (n=25) in comparison to the control period (n=10). There was also a significant increase in the proportion of button battery and magnet ingestions during the COVID-19 pandemic (p 0.04). Conclusion: These findings raise concerns of both increased frequency of foreign body ingestion during the COVID-19 pandemic and the nature of ingested foreign bodies linked with significant morbidity. This may relate to the disruption of home and work environments and carries implications for ongoing restrictions. Further awareness of the danger of foreign body ingestion, especially batteries and magnets, is necessary (project ID: 2956).